2021
DOI: 10.1158/2159-8290.cd-20-1109
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR/Cas9-Engineered ARID1A-Deficient Human Gastric Cancer Organoid Model Reveals Essential and Nonessential Modes of Oncogenic Transformation

Abstract: Mutations in ARID1A rank amongst the most common molecular aberrations in human cancer.However, oncogenic consequences of ARID1A mutation in human cells remain poorly defined due to lack of forward genetic models. Here, CRISPR/Cas9-mediated ARID1A knockout in primary TP53 -/human gastric organoids induced morphologic dysplasia, tumorigenicity and mucinous differentiation. Genetic Wnt/-catenin activation rescued mucinous differentiation, but not hyperproliferation, suggesting alternative pathways of ARID1A KO-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 91 publications
8
93
0
Order By: Relevance
“…© 2021 American Association for cancerdiscovery.aacrjournals.org Downloaded from differences. Interestingly, our data reconfirms the association of ARID1A-loss with the induction of mucinous phenotype, an observation first made by Lo et al(100) (Supplementary Figure7C).In conclusion, in one of the largest single-cell analyses of GC performed to date, our study forms a unique resource for generating novel biological insights on tumor cell types, subtype-based TME compositions and cell-cell interactions in gastric tumors. In terms of future directions, our data supports the need for further indepth studies on plasma cell homing biology guided by epithelial-KLF2, and the potential clinical implications of perturbing these interactions.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…© 2021 American Association for cancerdiscovery.aacrjournals.org Downloaded from differences. Interestingly, our data reconfirms the association of ARID1A-loss with the induction of mucinous phenotype, an observation first made by Lo et al(100) (Supplementary Figure7C).In conclusion, in one of the largest single-cell analyses of GC performed to date, our study forms a unique resource for generating novel biological insights on tumor cell types, subtype-based TME compositions and cell-cell interactions in gastric tumors. In terms of future directions, our data supports the need for further indepth studies on plasma cell homing biology guided by epithelial-KLF2, and the potential clinical implications of perturbing these interactions.…”
supporting
confidence: 89%
“…Amongst the platforms to study GC, PDOs have recently emerged as a promising system for ex vivo testing of therapeutic agents, precision oncology and assessing driver gene function (99,100). Our comparison of PDO-primary samples using scRNA-seq revealed that PDOs indeed maintained most major cell types, except for a depletion in lymphoid and plasma cell lineages.…”
Section: Discussionmentioning
confidence: 88%
“…An increasing number of studies indicated that the use of an organoid-based model could help reveal novel cancer driver genes [ 10 , 29 , 30 ]. Among the aforementioned three hub genes, CDK1 and CCNB2 promoted LUAD growth in this study, which were previously implicated in LUAD progression using cancer cell line models.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 These quadruple mutant organoids lost Wnt/R-spondin, EGF, and Noggin dependence and reliably formed invasive adenocarcinomas when xenografted. Similar modeling of other mutational cascades has provided insights into the development of cholangiocarcinoma, 56 breast, 57 pancreatic, 58 and gastric 59,60 cancers. Similarly, using CRISPR-Cas9 to precisely edit the genome of healthy organoids and induce particular disease phenotypes has yielded important insights into the causes of both polygenic and monogenic diseases.…”
Section: Organoids Reflect Cellular Characteristicsmentioning
confidence: 93%